2017
DOI: 10.1136/bjsports-2017-097508
|View full text |Cite
|
Sign up to set email alerts
|

The Concussion Recognition Tool 5th Edition (CRT5): Background and rationale

Abstract: Statistics: word count (excluding abstract, tables, and references):Author Note: To the editor-in-chief of BJSM, Dr. Karim Khan, the present paper has been commissioned by Professor Lars Engebretsen and is intended to be part of the BJSM IPHP theme issue on concussion in March 2017. This paper is internally reviewed by the expert group represented at the Berlin Consensus meeting on Concussion in Sport in October 2016. The SCAT5 assessment tool will be uploaded once artwork is complete.Page 3 AbstractThe Concus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 8 publications
0
57
0
2
Order By: Relevance
“…The Child SCAT5 is used to evaluate SRC in children 5–12 years old 14. A separate tool, the Concussion Recognition Tool 5 (CRT5),16 was developed for use by non-medically trained individuals to assist in the identification and initial management of suspected SRC. The designation of the SCAT5 (rather than SCAT4) was chosen to align the version number with the fifth meeting of the CISG.…”
Section: The Scat5mentioning
confidence: 99%
“…The Child SCAT5 is used to evaluate SRC in children 5–12 years old 14. A separate tool, the Concussion Recognition Tool 5 (CRT5),16 was developed for use by non-medically trained individuals to assist in the identification and initial management of suspected SRC. The designation of the SCAT5 (rather than SCAT4) was chosen to align the version number with the fifth meeting of the CISG.…”
Section: The Scat5mentioning
confidence: 99%
“…In lower levels of competition where trained medical staff are not available, off-field concussion screening tests are not recommended, and a 'recognise and remove' strategy is more appropriate, with immediate withdrawal from play when there is any degree of suspicion of concussion. [22] Previously administered as test cards, the KD test is now currently available only as a proprietary tablet application. Preceding studies have suggested differential baseline performance between these formats, and although unlikely, it is possible that diagnostic accuracy could also vary across these configurations.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…CRT5 = Concussion Recognition Tool 5; 9 , 10 SCAT5 = Sports Concussion Assessment Tool 5 11 . * For children aged 5–12 years 12 , 13 …”
Section: Boxmentioning
confidence: 99%
“…These tests are endorsed in the AIS–AMA position statement, which recommends that all parties involved in concussion management use the new, updated tools according to their purpose. These are the Concussion Recognition Tool 5th Edition (CRT5), 9 , 10 the Sports Concussion Assessment Tool 5th Edition (SCAT5) 11 and the Child SCAT5 for children aged 5–12 years 12 , 13 . The CRT5 replaces the old Pocket Concussion Recognition Tool and is intended for use by any member of the community to recognise the possible signs and symptoms of concussion when encountering a head injury.…”
Section: Boxmentioning
confidence: 99%